FESTIVALS AS SOFT POWER: ENHANCING THIRUVANANTHAPURAM’S GLOBAL CULTURAL IDENTITY - V. S. Anisha; O. Reegan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates how festivals in Thiruvananthapuram, Kerala act as instruments of soft power, fostering cultural diplomacy and strengthening global cultural identity. By analyzing major festivals like Attukal Pongala, Bhimapalli Uroos, Perunnal, Padmanabhaswamy Temple Festival and KTDC’s Onam celebrations, the study highlights their role in promoting communal harmony, tourism, and Kerala's intangible heritage. It also discusses challenges and provides policy recommendations to optimize the potential of festivals in enhancing the district’s global stature. Festival tourism becomes a harmonious symphony of cultural heritage preservation and community empowerment, celebrating the essence of a remarkable region.